Mathematics of DNA Structure, Function and Interactions - Benham, Craig John.; Harvey, Stephen; Olson, Wilma K.; Sumners, De Witt.; Swigon, David; SpringerLink (Online service) (New York, NY : Springer New York, 2009)
Propelled by the success of the sequencing of the human and many related genomes, molecular and cellular biology has delivered significant scientific breakthroughs. Mathematics (broadly defined) continues to play a major role in this effort, helping to discover the secrets of life by working collaboratively with bench biologists, chemists and physicists. Because of its outstanding record of interdisciplinary research and training, the IMA was an ideal venue for the 2007-2008 IMA thematic year on Mathematics of Molecular and Cellular Biology. The kickoff event for this thematic year was a tutorial on Mathematics of Nucleic Acids, followed by the workshop Mathematics of Molecular and Cellular Biology, held September 15--21 at the IMA. This volume is dedicated to the memory of Nicholas R. Cozzarelli, a dynamic leader who fostered research and training at the interface between mathematics and molecular biology. It contains a personal remembrance of Nick Cozzarelli, plus 15 papers contributed by workshop speakers. The papers give and overview of state-of-the-art mathematical approaches to the understanding of DNA structure and function, and the interaction of DNA with proteins that mediate vital life processes. .
Nick Cozzarelli: A Personal Remembrance -- Mathematical Methods in Dna Topology: Applications to Chromosome Organization and Site-Specific Recombination -- Conformational Statistics of Dna and Diffusion Equations on The Euclidean Group -- Perspectives On DNA Looping -- Differences Between Positively and Negatively Supercoiled DNA that Topoisomerases May Distinguish -- Calibration of Tethered Particle Motion Experiments -- Difference Topology: Analysis of High-Order DNA-Protin Assemblies -- Useful Intrusions of DNA Topology Into Experiments on Protein-DNA Geometry -- Topological Analysis of DNA-Protein Complexes -- Closing the Loop on Protein-DNA Interactions: Interplay Between Shape and Flexibility in Nucleoprotein Assemblies Having Implications for Biological Regulation -- Four-Way Helical Junctions in DNA Molecules -- Micromechanics of Single Supercoiled DNA Molecules -- Flexibility Of Nucleosomes On Topologically Constrained DNA -- The Mathematics of DNA Sturcture, Mechanics, and Dynamics -- Paradox Regained: a Topological Coupling of Nuclesomal DNA Wrapping and Chromatin Fibre Coiling -- Statistical-Mechanical Analysis of Enzymatic Topological Transformations in DNA Molecules.
Keywords: Medicine; Health informatics; Systems biology; Applied mathematics; Engineering mathematics; Biomathematics; Medicine & Public Health; Health Informatics; Mathematical and Computational Biology; Systems Biology; Applications of Mathematics; Electronic books